Towards universal social protection Lessons from the universal health coverage initiative - Rim, Ji-Yeun (OECD Publishing, 2019)
Universal social protection (USP) is becoming high priority in many developing countries' agendas. However, information on what has worked well - and not so well - is limited. This study reviews a wide range of recent country experiences with universal health coverage (UHC) financing and implementation in order to draw lessons and help governments elaborate policies for USP and the extension of social protection. It looks at different pathways and delivery and financing challenges to universalism in health coverage and takes a close look at equity issues. It concludes with some key takeaways from UHC implementation and its implications for USP. One important message of this study is that while the UHC experience cannot be mechanically transposed to the USP agenda, a number of lessons can be drawn. Moreover, the benefits in terms of coverage and equity of better integrating USP and UHC appear tremendous
Keywords: Development